2023
DOI: 10.1097/md.0000000000035692
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of endotracheal intubation in critically ill emergency patients with videolaryngoscopy

Chenghang Mo,
Liang Zhang,
Yingjiang Song
et al.

Abstract: To investigate the safety and efficacy of video laryngoscopy for endotracheal intubation in critically ill patients. A total of 106 critically ill emergency patients treated at our hospital between January 2021 and June 2022 were randomly divided into 2 groups, the visual and direct groups, with 53 patients in each group. Both groups were treated with endotracheal intubation; the visual group was treated with video laryngoscopy, and the direct group was treated with conventional direct laryngoscopy. The Cormac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Following the authors' search strategy, our reevaluation revealed that the study omitted several randomized controlled trials (RCTs) that met the criteria, including Mo et al [ 2 ], Shukla et al [ 3 ], Ilbagi et al [ 4 ], Grensemann et al [ 5 ], Kim et al [ 6 ], Silverberg et al [ 7 ]. These six additional RCTs increased the total patient count to 4532, with 2276 in the video laryngoscopy (VL) group and 2256 in the direct laryngoscopy (DL) group.…”
Section: To the Editormentioning
confidence: 99%
“…Following the authors' search strategy, our reevaluation revealed that the study omitted several randomized controlled trials (RCTs) that met the criteria, including Mo et al [ 2 ], Shukla et al [ 3 ], Ilbagi et al [ 4 ], Grensemann et al [ 5 ], Kim et al [ 6 ], Silverberg et al [ 7 ]. These six additional RCTs increased the total patient count to 4532, with 2276 in the video laryngoscopy (VL) group and 2256 in the direct laryngoscopy (DL) group.…”
Section: To the Editormentioning
confidence: 99%